Root exudates and chemotactic strains mediate bacterial community assembly in the rhizosphere soil of Casuarina equisetifolia L - Lin, Qi; Li, Miaomiao; Wang, Ying; Xu, Zhixia; Li, Lei (Frontiers in Plant Science, 2022)
Rhizosphere bacterial diversity and community structure are important factors involving in plant growth. However, the exact process of how plant rhizosphere bacterial community structures is assembled remains unclear. To investigate the role of bacterial chemotaxis to rhizosphere secretions in the establishment of rhizosphere microbial community in Casuarina equisetifolia, we screened bacteria strains derived from the rhizosphere of Casuarina equisetifolia L. using top three chemicals of the plant root exudates (2,4-di-tert-butylphenol, methyl stearate, and arginine) as chemoattractant. Among 72 bacterial strains, five showed strong chemotaxis to 2,4-di-tert-butylphenol, six to methyl stearate, and eleven to arginine, with the highest bacterial chemotaxis occurring at a concentration of 60 μM. This indicates that arginine is a more important chemoattractant than 2,4-di-tert-butylphenol, methyl stearate in the establishment of rhizosphere microbial community in Casuarina equisetifolia. Bacterial community assembly analysis using different chemoattractants and chemoattractants-plus-bacteria combinations were then performed by burying laboratory prepared bags of sterlized soil into C. equisetifolia forest. Bacteria diversity and enrichment analyses using 16S rRNA sequencing at 7 and 14 days after burying showed that arginine-plus-Ochrobactrum sp. and Pantoea sp. treatment exhibited the greatest similarity to the natural forest bacterial community. Our date provides new insights into how chemoattractants and chemotactic bacteria strains shape the rhizosphere microbial community of C. equisetifolia, which constitutes foundational information for future management of these communities.